PKP-010 Pharmacokinetic/pharmacodynamic evaluation of metronidazole and cefuroxime in prophylaxis of colorectal surgery. (24th February 2014) - Nogales, M; Isla, A; Hernanz, R; Martínez, S; Rodríguez, A; Saez de Ugarte, J; Martinez, C
Abstract : Background: The antibiotics used for prophylaxis in colorectal surgery (CS) must maintain appropriate plasma concentrations (PC) throughout surgery to avoid surgical site infections (SSI). Purpose: To determine the suitability of a single dose of metronidazole and cefuroxime for prophylaxis of CS, assessing the relation between antibiotic PC and the minimum inhibition concentration (MIC) of the microorganisms often isolated in SSI. Materials and methods: Prospective study involving 64 patients undergoing CS in a tertiary hospital. Each patient was given a single dose of 1.5 g metronidazole and 1.5 g cefuroxime by intravenous infusion over 20–60 min during induction of anaesthesia. 4–5 blood samples were taken; the first at the time of starting the infusion and one of them at the end of surgery. Mean duration of the operation was 2.68 h (range 0.75–6.83 h). We checked whether the dosing regimens used ensured concentrations of both drugs above the MIC of the microorganisms commonly isolated in SSI, during the whole intervention. The target concentration was 8 mg/L, the highest susceptibility breakpoint for bacteria expected to be found in these procedures. Results: Metronidazole PC at the time of closure of the peritoneal cavity ranged from 8.6 mg/L to 49 mg/L, all values above 8 mg/L. Cefuroxime PC at the time of closing ranged from 2.7 mg/L to 72 6 mg/L. In 6 cases, where surgery was prolonged over 2.6 h, the cefuroxime concentrations at closing time were less than 8 mg/L. Considering that the elimination half-life of cefuroxime is 1.3 h and after 2.6 h (two elimination half-lives) plasma levels fall below the target value, a second dose of 1.5 g of cefuroxime should be recommended in operations that extend over 2 h to ensure the target concentration throughout the intervention. Conclusions: A single dose of 1.5 g of metronidazole is able to maintain suitable levels of drug in the plasma for the entire surgery. In the case of cefuroxime, additional doses should be administered if the surgery is extended beyond 2 h. No conflict of interest.